Duelo del hijo ideal en cuidadores primarios tras el diagnóstico inicial de TEA. - Toro Rodas, Ashli Gabriela; Cruz Chamba, Wendy Nicole (My University, 2025)
he grieving process in mothers of children with Autism Spectrum Disorder (ASD) is a complex emotional experience that arises after diagnosis, when confronted with the difference between the idealized child and reality. This study was developed based on the principles of the systemic approach, supported by the theoretical contributions of Salvador Minuchin and John Bell, which offer a perspective focused on understanding problems and phenomena as complex systems. The objective is to understand the process of mourning the ideal child experienced by primary caregivers after their children are diagnosed with ASD. A qualitative approach was used, with a descriptive case study design and a cross-sectional scope, revealing that each mother experiences the grieving process in a unique way, showing great heterogeneity in emotional expression, expectations regarding motherhood, and the construction of their maternal identity. The sample consisted of four mothers who were caregivers of children diagnosed with ASD; these participants were selected through non-probabilistic convenience sampling in the cantons of Piñas and Huaquillas, in the province of El Oro (Ecuador). Significant data were obtained through the use of semi-structured interviews, direct observation, and a standardized instrument. It was confirmed that mothers experience a process of deep emotional grief following an autism diagnosis, with stages of denial, anger, and sadness, followed by transformative acceptance. It was concluded that, despite the multiple emotions they experience, such as guilt, anxiety, and isolation, they develop resilience, rebuilding their maternal identity and strengthening the bond with their children through love and commitment.
El proceso de duelo en madres de niños con Trastorno del Espectro Autista (TEA) es una experiencia emocional compleja que surge tras el diagnóstico, al confrontar la diferencia entre el hijo idealizado y la realidad. El presente estudio se desarrolló bajo los fundamentos del enfoque sistémico, sustentada en los aportes teóricos de Salvador Minuchin, John Bell que ofrecen una perspectiva centrada en la comprensión de los problemas y fenómenos como sistemas complejos. El objetivo es comprender el proceso de duelo del hijo ideal que experimentan las madres cuidadoras primarias tras el diagnóstico de TEA de sus hijos. Se empleó un enfoque cualitativo, con diseño de estudio de caso, de tipo descriptivo, con alcance transversal, revelando que cada madre vive el proceso de duelo de forma única, evidenciando una gran heterogeneidad en la expresión emocional, en las expectativas respecto a la maternidad y en la construcción de su identidad materna. La muestra estuvo compuesta por cuatro progenitoras, cuidadoras de niños diagnosticados con TEA; estas participantes fueron seleccionadas mediante un muestreo no probabilístico a conveniencia en el cantón Piñas y el cantón Huaquillas, provincia de El Oro (Ecuador). A través de la aplicación de: entrevista semiestructurada, observación directa e instrumento estandarizado, se obtuvieron datos significativos. Se corroboró que las madres experimentan un proceso de duelo emocional profundo tras el diagnóstico de autismo, con etapas de negación, ira y tristeza, seguidas de una aceptación transformadora. Se concluye que, a pesar de las múltiples emociones que vivencian como la culpa, ansiedad y aislamiento, desarrollan resiliencia, reconstruyendo su identidad materna y fortalecen el vínculo con sus hijos desde el amor y el compromiso.
Keywords: TEA; ÉTAPAS DEL DUELO; DIAGNÓSTICO; CARGA DEL CUIDADOR